2021
DOI: 10.1186/s41231-021-00101-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of autologous non-hematopoietic enriched stem cell nebulization in COVID-19 patients: a randomized clinical trial, Abu Dhabi 2020

Abstract: Background The novel SARS-CoV-2 has caused the coronavirus disease 2019 (COVID-19) pandemic. Currently, with insufficient worldwide vaccination rates, identifying treatment solutions to reduce the impact of the virus is urgently needed. Method An adaptive, multicentric, open-label, and randomized controlled phase I/II clinical trial entitled the “SENTAD-COVID Study” was conducted by the Abu Dhabi Stem Cells Center under exceptional conditional appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(52 citation statements)
references
References 46 publications
0
52
0
Order By: Relevance
“…All included studies were clinical trials, of which ten [ 15 – 24 ] were RCTs while other seven were NRCTs [ 25 31 ]. Four studies [ 16 , 17 , 23 , 24 ] were from the same clinical trial, and in addition to safety and efficacy of stem cell therapy, they also reported other characteristics such as radiological changes. Two studies [ 18 , 19 ] by Shu et al reported on the same trial, the first giving the outcome after 28 days and the second being the follow-up report after one year.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All included studies were clinical trials, of which ten [ 15 – 24 ] were RCTs while other seven were NRCTs [ 25 31 ]. Four studies [ 16 , 17 , 23 , 24 ] were from the same clinical trial, and in addition to safety and efficacy of stem cell therapy, they also reported other characteristics such as radiological changes. Two studies [ 18 , 19 ] by Shu et al reported on the same trial, the first giving the outcome after 28 days and the second being the follow-up report after one year.…”
Section: Resultsmentioning
confidence: 99%
“…For RCT studies, two of them [ 20 , 21 ] lacked comprehensive information on random sequences in the original text, and one study [ 16 ] had obvious missing data. The study by Zhu, R et al [ 20 ] adopted a single-blind method, and the study by Yendry Ventura‑Carmenate et al [ 16 ] is an open-label trial, therefore, the item of blinding of participants and personnel were rated as high risk for these studies. For NRCT studies, all seven of them had control groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations